EFL Learner's Strategies to Build Self-Confidence in Speaking: A Narrative Inquiry - Arifin; Siti Mafulah; Agus Sholeh (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2025)
Building self-confidence is essential for developing effective speaking skills in English as a Foreign Language (EFL). This study explores the strategies of an EFL learner to enhance his self-confidence in speaking and examines the challenges he faces in the process. The participant was an Indonesian graduate student from Gadjah Mada University, and data were collected through semi-structured interviews to provide qualitative insights. Narrative inquiry was used to analyze the responses, while thematic analysis was applied to identify key patterns. The findings revealed that memory strategy, prepared talk, and extramural English exposure were particularly effective in building self-confidence in speaking. Of these, extramural English exposure played a significant role in boosting the participant's speaking confidence. However, challenges such as limited vocabulary, comprehension difficulties, and inconsistent language practice were noted. A major barrier was the lack of vocabulary, which undermined the participant's confidence in speaking. This study provides valuable insights for language learners aiming to improve their speaking confidence and offers implications for teachers in refining their teaching methods to support learners' needs.